BEHAVIORAL MANAGEMENT IN DENTAL CARE FOR A PATIENT WITH MULTIPLE COMORBIDITIES: A CASE REPORT - Graeff, Amanda de Freitas (2025)
This case report describes the dental approach to an adult female patient diagnosed with spastic diplegic cerebral palsy, developmental disorders, visual impairment, intellectual disability, and other associated neurological conditions. The aim was to detail the behavioral and clinical management strategies implemented at the Clinic for Special Care Dentistry, at the Federal University of Rio Grande do Sul (UFRGS), Brazil. The treatment was planned and performed monthly starting in November 2024, focusing on adapted communication, reduction of sensory stimuli, positive reinforcement techniques, and oral hygiene education for the caregiver. Improved patient cooperation was achieved without the need for sedation or general anesthesia. It is concluded that an individualized and humanized approach allows for safe and effective treatment in patients with multiple comorbidities.